2014
DOI: 10.1038/jes.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of occupational exposure to electric shocks and magnetic fields and mortality from amyotrophic lateral sclerosis in the US, 1991–1999

Abstract: We investigated the relationship between occupational exposure to electric shocks (ES) and magnetic fields (MF) and amyotrophic lateral sclerosis (ALS) using 1991-1999 US mortality data. For each of the 5886 included ALS deaths, 10 controls-matched on sex-, age-, year- and region-were selected from among other deaths. Usual occupation as reported on death certificates was linked to job-exposure matrices for ES and MF. Education and electric occupations were associated with moderately increased ALS risks (odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Focusing only on the first aspect (vaporized metals), we used risk rates based on years at work with welding and the weighted RR was 0.95 (95% CI 0.70–1.29), (Figure 5) [22,23,27,32,40,48,51,54]. The heterogeneity was apparent and leaving out the big study by Feychting [22], it was reduced from 82% to 77%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Focusing only on the first aspect (vaporized metals), we used risk rates based on years at work with welding and the weighted RR was 0.95 (95% CI 0.70–1.29), (Figure 5) [22,23,27,32,40,48,51,54]. The heterogeneity was apparent and leaving out the big study by Feychting [22], it was reduced from 82% to 77%.…”
Section: Resultsmentioning
confidence: 99%
“…The exposures can be separated into electrical accidents/trauma and electromagnetic fields (EMF) per se. The level of EMF exposure was estimated through a job exposure matrix (JEM) established by occupational hygienists [22,31,32,33,39,40,41,44,47,54], and the weighted RR was 1.23 (95% CI 1.04–1.45), which is statistically significant (Figure 6). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study published after the meta-analyses, Sorahan and Mohammed (2014) found no convincing evidence of a higher risk for motor neurone disease in a cohort of electricity supply workers in the UK. Three subsequent studies reporting on exposure to ELF-MF and risk of ALS including information on electrical shocks have found contradicting results: Vergara et al (2015) observed an association between electric occupations and risk of ALS, but no association to electric shocks or magnetic fields, while Huss et al (2015b) reported an association between magnetic fields and ALS, but no association to electric shocks and Fischer et al (2015) found no association between electric occupations and ALS, but a weak association between electric shocks and ALS.…”
Section: Comparison With Previous Follow-ups In the Cohort And Othermentioning
confidence: 97%